PENGARUH SERVICE QUALITY TERHADAP COMPETITIVE ADVANTAGE MELALUI STUDENT LOYALTY DAN UNIVERSITY REPUTATION SEBAGAI VARIABEL INTERVENING - Kristianto Kevin (Business Accounting Review, 2015)
This study is aims to examine the effect of service quality to competitive advantage with student loyalty and university reputation as intervening variables. Data that used in this study are primary data. This study use students from 6 private universities in Surabaya as samples with purposive sampling method. Hypotheses in this study is analyzed using structural equation model (SEM) with SmartPLS 2.0. The result revealed that, service quality significantly affect competitive advantage directly, and indirectly through intervening variables which are university reputation and student loyalty.